The Puzzle of Grammatical Gender: Insights from the Cognitive Theory of Translation and the Nature of Polish Hybrid Nouns - Drzazga, Grażyna (My University, 2013)
The category of grammatical gender has gained considerable attention in the linguistic literature. Previous studies focused primarily on describing the often very complex system of genders in particular languages, on the understanding of the category per se (e.g. the origin of gender differentiation) or the acquisition of grammatical gender and the processing of this category in language production.
In contrast, the present dissertation looks at grammatical gender from a cognitive point of view. For the sake of this dissertation, cognitive perspective is defined as the assumption that human language cannot be separated from the way human beings perceive the world since language and thought are inextricably related. This approach also implies that research cannot be limited to theoretical explorations, but rather, that it must employ experimental methods and use research tools traditionally associated with other disciplines to collect data about authentic language use. All studies included in this thesis concentrate on the topic of grammatical gender, but they approach the category from a variety of perspectives.
It was found that the grammatical gender, at least to some degree, shapes the worldview of speakers of those languages in which the category operates, since the gender of the personification of concepts usually agrees with the grammatical gender of the respective nouns. In the context of translation, grammatical gender proved to be much more challenging than had been expected; there were many mistakes found in the translation product and many hesitations observed in the translation process.
The findings of the studies included in this thesis add to the general understanding of the complexities of the category of grammatical gender and its relationship to the way language users perceive the world. What is more, the investigations and proposals presented here emphasize the need for a more interdisciplinary approach to the study of grammatical gender.
Keywords: grammatical gender; translation process; hybrid nouns; gender assignment; personification of death; Modern Languages; Modern Languages